Beyond Alternative Food Networks: Understanding Motivations to Participate in Orti Urbani in Palermo. (11th April 2019) - Migliore, Giuseppina; Romeo, Pietro; Testa, Riccardo; Schifani, Giorgio
Abstract: Community gardens include many benefits, and different motivations seem to underline citizens' choices to participate. In Italy, political motivations are considered one of the main reasons for participation in community gardens (known as orti urbani ). Drawing from the orti urbani experience in Palermo (the largest city in Sicily, Southern Italy), this study aims to understand the main motivations that influence citizens' participation and to measure the effects of these motivations on fruit and vegetable consumption among participants. Findings reveal that orti urbani attract middle‐class participants who possess high amounts of cultural capital but relatively less financial capital. Among the motivations affecting the citizens' participation, eating safe food is the most important one. Orti urbani represent a solution to the increasing concerns about the safety of food and the urban environment.